Differences in Job Satisfaction Between Permanent Employees and Outsourcing Employees of PT. Domusindo Perdana - Dinda Tira Virratih; Widyastuti Widyastuti (Proceedings of The ICECRS, 2020)
This research is motivated by the phenomenon of employees who feel they lack the rights as employees in the company.This study aims to determine differences in job satisfaction between permanent employees and outsourced employees of PT. Domusindo Perdana. This research is a comparative quantitative study. The population in this study was 1,242 employees. This study uses a sample of 200 employees with details of 100 permanent employees of PT. Domusindo Perdana and 100 outsourced employees of PT. Domusindo Perdana. The sampling technique used in this study is quota sampling technique. Data collection techniques in this study used a job satisfaction scale consisting of 41 items. The hypothesis in this study is that there are differences in job satisfaction between permanent employees and outsourced employees of PT. Domusindo Perdana. The results in this study indicate that the value of permanent employee job satisfaction (mean rank: 130.78) is higher than the value of outsourcing employee satisfaction (mean rank: 70.22) with a significance value of 0,000 <0.05 which indicates that there are differences in satisfaction work between permanent employees and outsourcing employees of PT. Domusindo Perdana.